Simulasi Pembuatan Etil Asetat Menggunakan ReactiveDividing Wall Column Dengan Katalis Asam Sulfat - Johannes Martua Hutagalung (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Reactive Dividing Wall Column (RDWC) is an innovation which integrate reaction and distillations into one unit. The purpose of this study aims to simulate both reboiler duty and distillate rate to obtain the purity of ethyl acetate, water, and acetic acid in the stream products usingAspen Plus simulation software. RadFrac modul is used to model vapor –liquid equilibrium in the column and NRTL model is used to calculate thermodynamic properties in the liquid and vapor phases. The model has been validated by comparing both temperature as well as product composition profiles to those of open literature. The simulation results show that varying the distillate rate (D) and reboiler duty (Qr) will affect the purity of distillate components (ethyl acetate), side product (water) and bottom component (acetic acid). Based on maximum purity ofethyl acetate, the operating conditions are respectively recommended at distillate rate of 74.902 mole/h and reboiler duty of 1.93 kW. The product compositions are 73.69 mol% ethyl acetate, 90.21 mol% water and 42.98 mol%acetic acid.